Еndothelial dysfunction due to sodium nitrite - Savitsky, I. V.; Kryukovа G. V.; Myastkivska, I. V.; Gerasymenko, T. V.; Moiseieva, G.; Yermuraki, P. (Journal of Education, Health and Sport, 2020)
In the report of the World Health Organization from 1990 to 2016 to this day, Ukraine continues to occupy first place in the European region in morbidity and mortality from diseases of the cardiovascular system. One of the predictors and key links in the development of CVD is endothelial dysfunction. In this work, it was shown that chronic loading with sodium nitrite provokes the development of oxidative stress (an increase in 2,3-bisphosphoglyceric acid), inflammation (an increase in the level of interleukin-1-beta, which, in turn, causes a sharp increase in iNOS activity), the development of endothelial dysfunction (increase in von Willebrand factor). L-arginine alone, and in conjunction with the drug “Vin-Vita” cause a decrease in the negative effect of sodium nitrite.